TREE COMMUNITY STRUCTURE AND COMPOSITION OF A ONE HECTARE PERMANENT PLOT IN THE MONTANE ZONE OF MOUNT KERINCI, KERINCI SEBLAT NATIONAL PARK, JAMBI - NASUTION (NIM : 20615004), TAUFIKURRAHMAN
Information on tree community structure and composition as the main component of forest biodiversity is needed in forest management and restoration. Establishing a permanent plot for long term monitoring is one approach to obtain this data. Permanent plot can facilitate gathering time series data including demographic parameters and other species specific characteristics. These characters are important in selection of local species for commercial and restoration purposes. This study aims to (i) describe tree community structure and composition of permanent plot in a first data census for long-term study of montane forest dynamics, (ii) evaluate ecological condition of forest in permanent plot and (iii) analyse implication of this study for forest conservation and restoration. Data collection was conducted from July to August 2016 in the montane zone of Mount Kerinci, Kerinci Seblat National Park, Jambi. A one hectare permanent plot was established at 2,182 - 2,258 m above sea level and subdivided into 100 subplots of 10 x 10 m2. All trees species with diameter of more than 10 cm were permanently tagged and numbered. Tree parameters measured were diameter at breast height (DBH), height and position. Herbarium vouchers of all tree species were collected and identified into species level. This study recorded 570 individual trees belonging to 28 species, 18 genera and 20 families. Tree diversity as measured by Shannon - Wiener diversity index was 2.89. Species evenness was relatively low and indicated by domination of only five species in term of relative abundance that represented 50.35% of total abundance. Myrtaceae and Fagaceae had the highest species richness with three species of trees. Simulation of species area curve Estimates ver.9.1.0 showed that the one hectare permanent plot was occupied by most of the tree species (93.33%) predicted to be found in the study area. Species with the high species important value index (more than 10%) were Syzygium lineatum, Exbucklandia populnea, Syzygium pyrifolium, Turpinia montana, Polyosma integrifolia, Castanopsis javanica, Callicarpa longifolia, Macropanax dispermus, Magnolia calophylloides, Syzygium fastigiatum, Lithocarpus elegans and Prunus arborea. Distribution patterns of tree species were clumped (17 species), uniform (seven species) and random (one species). The family with the highest IVI was Myrtaceae followed by Fagaceae and Hamamelidaceae. The average wood density of all trees was 0.63 + 0.13 g cm-3, which is relatively high and indicated the domination of slow growing species. The distribution of individuals by DBH class formed inverted J-shaped curve indicating natural forest with good capacity of forest regeneration. Vertical structure of forest showed a stratification with four strata with the most abundance species found in stratum C (10 - 20 m). The total basal area was relatively high (51.45 m2 ha-1) and the contribution of large trees of more than 50 cm DBH was higher than small and medium trees (58.79%). The aboveground biomass (AGB) estimation using regression models with and without tree height were 361.30 Mg ha-1 and 463.13 Mg ha-1 respectively. There were five species of trees showed hyperdominancy in contribution of total biomass in study area. Those were Exbucklandia populnea, Castanopsis javanica, Lithocarpus elegans, Syzygium lineatum and Syzygium pyrifolium and they represented 57.36% of total biomass. Large trees of more than 50 cm DBH had the highest contribution and represented 64.79% of total tree biomass. The average canopy coverage was relatively high (72.86 + 4.99%) and this influenced microclimate as indicated by low air temperature (13.77 + 2.400C) and high relative air humidity (97.49 + 6.27%). Based on a number of parameters of tree community structure and composition, it can be concluded that the forest in the permanent plot was a less disturbed primary forest. This permanent plot can be used as a reference area in restoration activities in the same altitudinal zone. Of the species found in the permanent plot, ten species of climax tree and four species of pioneer tree can be recommended for forest restoration using framework method restoration. Those species were Garcinia lateriflora, Castanopsis javanica, Lithocarpus monticolus, Lithocarpus elegans, Exbucklandia populnea, Callicarpa longifolia, Magnolia calophylloides, Syzygium lineatum, Syzygium pyrifolium, Turpinia montana, Vernonia arborea, Ficus serraria, Ficus lepicarpa and Schima wallichii.